Peningkatan Pemahaman Orangtua untuk Mengembangkan Minat Belajar Anak Usia Dini Pada Program Pembelajaran Jarak Jauh (PJJ) Masa Pandemi Covid-19 - Laelillah, Resty Hasby; Salsabilla, Nadya Yulianty (Publikasi Pendidikan, 2023)
Distance learning (PJJ) began to be implemented by the Ministry of Education and Culture in Circular No. 4 of 2020 concerning the implementation of education policies in the emergency period of the spread of coronavirus Disease (Covid-19). From the distance learning program as a government policy. Researchers found a phenomenon that appeared in Wanayasa village, especially in SPS schools in Wanayasa Village which experienced many obstacles when carrying out the PJJ program. The purpose of this Community Service is to provide solutions for parents, teachers, and school principals in overcoming and growing interest in early childhood learning during the Covid-19 Pandemic. The method that the researcher provides in this community service activity uses a socialization and education approach with presentation and consultation methods to parents, teachers, and school principals. The results of the socialization and education activities for SPS schools in Wanayasa Village are that parents and teachers who participate in this socialization have been able to overcome how to grow children's interest in learning during distance learning at home, as well as teachers can overcome obstacles that will be faced when implementing the program. PJJ. The results of this socialization and education activity indicate that there is an increase in knowledge in how to foster interest in early childhood learning during the pandemic with distance learning (PJJ)